2014
DOI: 10.1177/0021934714557329
|View full text |Cite
|
Sign up to set email alerts
|

The African Union’s Call for Global Pan-Africanism and the Ghana-Diaspora Relations in the 21st Century

Abstract: One of the most outstanding initiatives that the African Union (AU) has taken that distinguishes it from its predecessor (the Organization of African Unity) is the adoption of the African diaspora as its sixth region. This article has two principal sections. First, by establishing the reasons for adopting the African diaspora as its sixth region from development perspectives, it explores how the African diaspora can engineer development processes in Africa and the challenges that the AU must address if the Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…they establish a meaningful connection with the outside world. It could be suggested that this is representative of modern-day Africa, as, like Bolaji (2015) has explained, the increased availability and accessibility of affordable mobile phones has connected Africa and its diaspora in a way that has never been possible thus far. Anna-Leena Toivanen states that "communication technologies enable the intertwinement of the local and the global", especially in how it is represented within literature and popular culture (2016, p. 138).…”
Section: Kimoyo Beads the Djalia And The Egungunmentioning
confidence: 94%
“…they establish a meaningful connection with the outside world. It could be suggested that this is representative of modern-day Africa, as, like Bolaji (2015) has explained, the increased availability and accessibility of affordable mobile phones has connected Africa and its diaspora in a way that has never been possible thus far. Anna-Leena Toivanen states that "communication technologies enable the intertwinement of the local and the global", especially in how it is represented within literature and popular culture (2016, p. 138).…”
Section: Kimoyo Beads the Djalia And The Egungunmentioning
confidence: 94%
“…However, South Africa has been able to expand its economic might across Africa. Although, Ghana provides a political base for Pan-Africanism due to the intellectual foundation laid by Kwame Nkrumah (Bolaji, 2015), South Africa has strategically occupied the leadership position of the regional supranational body: Africa Union. The possibility of deeper integration, led by the African Union headed by a South African, Nkosazana Dlamini-Zuma, would serve the interests of the rainbow nation.…”
Section: Hegemony or Leadership: The Dilemma Of Theory And Practicementioning
confidence: 99%
“…Improvement in human development and poverty reduction could also in turn enhance conflict prevention and peacebuilding in Africa. (Bolaji, 2015;Edo and Olanrewaju, 2012;Manby, 2004). Both Lehman (2007Lehman ( , 2005 and Ampiah ( 2005) also rightly note that AU and NEPAD's emphasis on the need for Africa to take a lead and/or strategic partnership in the continent's development process significantly keyed into the primary focus of the TICAD on ownership and partnership.…”
Section: B Ticad Ii: Human Development and Poverty Reduction Via Economicmentioning
confidence: 99%